2007
DOI: 10.1007/bf02802096
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of successful weight reduction after bariatric surgery by data mining technologies

Abstract: Artificial neural network is a better modeling technique and the overall predictive accuracy is higher on the basis of multiple variables related to laboratory tests. LMGB, high preoperative triglyceride level, and low HbAlc level can predict successful weight reduction at 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Excess body weight loss 1 year after surgery (74%) was roughly similar to that of other published series using similar surgical techniques. Age and BMI were negative predictors of weight loss in many, but not all [12,26], previously reported BS studies [27][28][29][30][31][32][33][34]. EWL has been reported to be greater in females [17,27,29,34], greater in males [29,32], or no gender differences have been shown [26,28,31,33].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Excess body weight loss 1 year after surgery (74%) was roughly similar to that of other published series using similar surgical techniques. Age and BMI were negative predictors of weight loss in many, but not all [12,26], previously reported BS studies [27][28][29][30][31][32][33][34]. EWL has been reported to be greater in females [17,27,29,34], greater in males [29,32], or no gender differences have been shown [26,28,31,33].…”
Section: Discussionmentioning
confidence: 82%
“…We are aware of only one study that evaluated the association between baseline HbA1c and TG with EWL after BS [26]. This study, in which diabetic status was not reported, showed that people in the successful group had lower baseline HbA1c but higher TG concentrations [26]. Some limitations of our study should be acknowledged.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Some predictive factors of poor weight loss after gastric banding surgery have been identified in previous studies [7][8][9][10]. Similarly, after gastric bypass, several preoperative predictors of poor weight loss have already been identified such as initial weight or body mass index [6,[11][12][13][14], advanced age [13,15], and female gender [13,16].…”
Section: Introductionmentioning
confidence: 91%
“…Table 4 expresses test index of established logistic model. The model had a significant effect on weight reduction (Sig=0.000) by regression analysis [17] .…”
Section: Establishing Logistic Regression Modelmentioning
confidence: 99%